The Effect of mechanical unloading on TRAF6 and MuRF1 genes expression in soleus muscle of male Wistar rats - abdolreza kazremi; zahra masoumpor; amirbahador dakhili; Alireza Zangiabadi; Iman fathi (Shahid Beheshti University, 2021)
Purpose: Because of exiting uncertainties in growth and maintenance of muscle mass processes, particular atrophy inducing inactivity, the aim of the present study was to investigate changes in the expression of atrogenic genes in the muscle of the rat in which the hind-limbs were kept under unloaded conditions. Methods: For this purpose, 10 male Wistar rats were assign in two groups of suspension (n=5) and control (n=5) and the suspension group rats were kept for two weeks in this conditions. After 14 days, the soleus muscle was extracted and the expression of TRAf6 and MuRF1 genes was measured by real-time-Pcr method. Results: The results of this study showed that after 14 days of hind-limb suspension, the relative weight of soleus muscle was significantly decreased (P=0.009). In addition, the expression of TRAF6 gene was significantly increased (P=0.033), but MuRF1 was not statistically significant (P=0.061). Conclusion: Therefore, according to the results of this study, it can be stated that TRAF6 and its downstream factor, MuRF1, can be involved in the regulation of muscle mass in conditions of reduced muscular activity and mechanical unloading and as candidates for controlling muscle mass in conditions such as athlete's hospitalized after sports injuries or hind-limb unloading after injury to be considered.